Досвід хірургічного лікування розшаровуючих аневризм грудної аорти типу A за 2010–2012 - Кравченко, І.М.; Ситар, Л.Л.; Кравченко, В.І.; Третяк, О.А.; Литвиненко, В.А.; Бацак, Б.В.; Осадовська, І.А.; Захарова, В.П.; Маарі, Ахмед; Тарасенко, Ю.М.; Книшов, Г.В. (Таврический медико-биологический вестник, 2013)
Одной из наиболее сложных и актуальных проблем сердечно-сосудистой хирургии является острое расслоение аорты типа А. Частота возникновения острой расслаивающей аневризмы грудной аорты составляет 5–20 случаев на 1млн населения в год, при этом тип А составляет до 75% случаев. One of the most difficult and actual problems of cardiovascular surgery is acute thoracic aortic dissection of type of A (TAAD). The frequency of occurrence of acute aortic dissection aneurysms is 5–20 cases on 1 mln the population per year, thus type A conclude up to 75 % of cases. Present our experience of surgical treatment of type A TAAD during 2010 – 2012 – the aim of this study.